Inter-Organizational Mobility Among Female Technologist In Malaysian Industry - Kadir, O.; Omar, M. Z.; Zaharim, A.; Rasul, M. S. (International Journal of Advanced Science and Technology, 2019)
Student entrance to higher education institution in Malaysia based on merit have resulted the institution being dominated by women. This phenomenon has caused many of engineers and technologists in the industries are women. However, inter-organizational mobility often occurs among these technical women which result in the loss of valuable human resources to the organization and thereby trigger the issue of product design secrecy. A study was conducted to identify factors affecting the inter-organizational mobility among female engineering technology graduates. Based on previous studies, female graduates are more likely to inter-organization mobility which is more focused on subjective career success whereas men are more likely focused on objective career success. Therefore, based on the theory of protean career, this study was conducted to examine the relationship between work-life balance, psychological well-being towards organization mobility among 114 female engineering technology graduates in the Malaysian industry. A model has been developed and tested using structural equation modeling techniques using SmartPLS software. The findings show that there is a negative relationship between work-life balance towards organization mobility as well as psychological well-being towards organization mobility. The new finding in this study is psychological well-being plays a major role in organization mobility compared to work-life balance. Therefore, employers should be aware of the importance of psychological well-being and work-life balance to female technologist in industry. Employers should formulate related policies regarding work-life balance at the workplace to reduce inter-organizational mobility by female technologists. As such, aspects of psychological well-being should be emphasized by employers which can enhance the excitement of employees and be productive workers.